Anti-confocal assessment of middle ear inflammation - Jung, David S.; Crowe, John A.; Birchall, John P.; Somekh, Michael G.; See, Chung W. (Optical Society of America, 2016)
To improve the diagnostic prediction of recurrence of otitis media with effusion after surgery, an anti-confocal system combined with spectroscopic measurements is proposed to reject unwanted signals from the eardrum and assess the blood content. The anti-confocal system was experimentally evaluated on both optical middle ear phantom and human skin. Results showed effective rejection of signals from the eardrum using a central stop replacing the confocal pinhole, while still detecting signals from the middle ear mucosa. The system is sensitive to changes in blood content, but scattering and absorption characteristics of the eardrum can distort the measurement. Confocal detection of eardrum properties was shown to be a promising approach to correct measurements.